PENGARUH INOVASI DIGITAL TERHADAP PEMBELAJARAN BAHASA DI SEKOLAH DASAR: ANALISIS BIBLIOMETRIK - Ismail Ismail; Azra Fauzi; Abas Oya; Nurwalidainismawati Nurwalidainismawati (STKIP HARAPAN BIMA, 2024)
This study aims to identify and analyze trends in digital innovation in language learning in primary schools during the period from 2019 to 2024. Digital innovation plays a key role in improving students' language skills through interactive media, video-based technologies, and Android-based applications. This study used bibliometric analysis to explore publications related to this topic, with data obtained from Crossref via the Publish or Perish application and analyzed using tools such as VOSviewer. The results of the study show that the number of publications related to digital innovation in language learning has significantly increased over the past five years. The highest number of publications occurred in 2023 with 290 documents, reflecting a surge in research during the COVID-19 pandemic. Conversely, the lowest number of publications was recorded in 2019, with only 40 documents published. The study also found that audio-visual learning media and video-based learning are the most widely used technologies, making a significant impact on the effectiveness of language teaching. The main challenges identified are the limitations in teacher preparedness and infrastructure to support the integration of technology in the teaching process. This study has implications for the importance of developing teacher skills in using digital technology and provides opportunities for further research on the long-term effects of digital innovation in language learning in primary schools.